The Role of Leadership in Managing Change - Musaigwa, Misheck (International Review of Management and Marketing, 2023)
Organisational change is a sophisticated and challenging process. As a result, many organisations that embark on change initiatives fail to achieve their intended goals and sometimes change leads to high costs, which undermine its benefits. However, despite these challenges, it is becoming increasingly important for organisations to embrace change for their survival and success owing to the dynamic and rapidly changing business environment caused mainly by technological advancement. This research aimed to investigate the role of leadership in managing change. The study employed a qualitative approach and drew a sample of 10 participants who are department managers. These candidates perform managerial and leadership responsibilities in the organization understudy. The study employed purposive sampling and thematic analysis to analyse the data. The findings suggested that leadership plays a fundamental role in change management. The leadership roles found include motivating employees, creating a vision for change, communicating change, planning for change, creating a conducive environment for change, getting employees’ buy-in and leading staff by example.